Strategy BMT Al-Ittihad Using Matrix IE, Matrix SWOT 8K, Matrix Space And Matrix Twos - Nofrizal Denan (Universitas Muhammadiyah Surabaya, 2018)
This research aims to formulate and select BMT Al- Ittihad Rumbai strategy to face the changing of business environment both from internal environment such as organization resources, finance, member and external business such as competitor, economy, politics and others. This research method used Analysis of EFAS, IFAS, IE Matrix, SWOT-8K Matrix, SPACE Matrix and TWOS Matrix. our hope from this research it can assist BMT Al-Ittihad in formulating and selecting strategies for the sustainability of BMT Al-Ittihad in the future. The sample in this research is using purposive sampling technique that is the manager and leader of BMT Al-Ittihad Rumbai Pekanbaru. The result of this research shows that the position of BMT Al-Ittihad using IE Matrix, SWOT-8K Matrix and SPACE Matrix is in growth position, stabilization and aggressive . The choice of strategy after using TWOS Matrix is market penetration, market development, vertical integration, horizontal integration, and stabilization (careful.)